Oxford Online Database of Romance Verb Morphology - Maiden, M (University of Oxford, 2010)
The database was created as one outcome of the AHRC-funded research project 'Autonomous Morphology in Diachrony: comparative evidence from the Romance languages' (AH/D503396/1), 2006-2010